2015
DOI: 10.14434/pders.v34i1.13823
|View full text |Cite
|
Sign up to set email alerts
|

A Module-Based Approach: Training Paraeducators on Evidence-Based Practices

Abstract: Paraeducators are on the front lines in special education settings, providing support to teachers and students with significant disabilities and specific health-care needs. The important role they play demands efficient and cost-effective training in core skills. This study utilized a multiple-baseline across behaviors design to evaluate a module-based training program for paraeducators targeting three instructional strategies that are commonly used in the education of students with a wide range of disabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…QIs 7.4 (three data points per phase) and 7.5 (e.g., IOA ≥80%) were each met by 42 studies (87.50%). For example, Da Fonte and Capizzi (2015) had four or more data points per phase and observed 36% of sessions across phases and participants for IOA, which was consistently above 90% (range = 88%–100%). QI 7.6 was applicable to group designs and was met by Wright et al (2012) through demonstration of construct and social validity.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…QIs 7.4 (three data points per phase) and 7.5 (e.g., IOA ≥80%) were each met by 42 studies (87.50%). For example, Da Fonte and Capizzi (2015) had four or more data points per phase and observed 36% of sessions across phases and participants for IOA, which was consistently above 90% (range = 88%–100%). QI 7.6 was applicable to group designs and was met by Wright et al (2012) through demonstration of construct and social validity.…”
Section: Resultsmentioning
confidence: 97%
“…In particular, as many teachers report a lack of training in classroom management in teacher preparation programs (e.g., Chesley & Jordan, 2012), using low-intensity strategies such as BSP is one manageable approach to improving classroom management practices and creating a positive and supportive classroom environment. Furthermore, additional inquiry exploring the role of coaching on the delivery of praise by paraprofessionals (e.g., Da Fonte & Capizzi, 2015) and preservice teachers (e.g., Morgan et al, 1994; Rathel et al, 2008) can help support the use of BSP by these educators. We hope teacher preparation programs and university faculty will use this information to inform instruction and support implementation of BSP and other low-intensity strategies in their coursework.…”
Section: Discussionmentioning
confidence: 99%
“…Kalis and colleagues (2007) assessed social validity through postintervention interviews and by comparing student grades pre- and postintervention. Social validity was assessed through surveys or questionnaires ( k = 27, 81.81%; e.g., DaFonte & Capizzi, 2015; Pinter et al, 2015), interviews ( k = 4, 12.12%; e.g., Alexander et al, 2012; Haydon & Musti-Rao, 2011), preservice teacher journal comments ( k = 2, 6.06%; Rathel et al, 2014; Rathel et al, 2008), and student outcomes ( k = 2, 6.06%; Kalis et al, 2007; Ploessl & Rock, 2014). All studies reporting social validity outcomes indicated treatment acceptability.…”
Section: Resultsmentioning
confidence: 99%
“…Only studies with BSP as a primary DV or IV were included, as praise was often a part of an intervention but not the focus of the investigation (e.g., functional assessment–based interventions; Lane et al, 2007). If other strategies were a part of the investigation (e.g., multiple baseline across teacher behaviors where BSP was a separate tier; Barton, Fuller, & Schnitz, 2016; Da Fonte & Capizzi, 2015), BSP data had to be reported separately to be included in our review.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the Council for Exceptional Children’s (2004) Paraeducator Workbook recommends ongoing professional development through local schools and state agencies. Many school districts are now moving toward module-based online professional development (Da Fonte & Capizzi, 2015; Douglas, McNaughton, & Light, 2013) due to the reduction of funding and, in the case of rural areas, access to face-to-face professional development. Although many models are in place, Garet, Porter, Desimone, Birman, and Yoon (2001) found that sustained and intensive professional development is the most effective type of training for educators as compared with shorter professional development.…”
Section: Professional Development Modelsmentioning
confidence: 99%